2018
DOI: 10.1002/vnl.21668
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nano‐Sb2O3/poly(butylene terephthalate) composite powders based on high‐energy ball milling

Abstract: In this work, a kind of composite powders with good dispersion and distribution of nano-Sb 2 O 3 particles in poly(butylene terephthalate) (PBT) was prepared by the high-energy ball milling (HEBM). The effects of the milling time on the structure, morphology, particle size distribution, and thermal behavior of the nano-Sb 2 O 3 /PBT composite powders were characterized by Fourier transform infrared spectroscopy, scanning electron microscope, laser diffraction particle size analyzer, and thermal analysis (TGA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, two T g s were attained in the case of the nanocomposite powders when the milling time was over 3 hours, one of them being slightly higher than that of the pure PBT, which showed that there was a special interaction between PBT and nano-Sb 2 O 3 particles. However, the HEBM process led to a decrease of the PBT crystallinity (Yang et al 2018(Yang et al , 2019. The authors further explained (PBT) nanocomposites contained modified nano-Sb 2 O 3 particles were dispersed by two different dispersing techniques, included high speed rotating to disperse (HSR) and high-energy ball milling to disperse (HEBM).…”
Section: Hebm In Thermoplastic Matrix Compositesmentioning
confidence: 99%
“…Furthermore, two T g s were attained in the case of the nanocomposite powders when the milling time was over 3 hours, one of them being slightly higher than that of the pure PBT, which showed that there was a special interaction between PBT and nano-Sb 2 O 3 particles. However, the HEBM process led to a decrease of the PBT crystallinity (Yang et al 2018(Yang et al , 2019. The authors further explained (PBT) nanocomposites contained modified nano-Sb 2 O 3 particles were dispersed by two different dispersing techniques, included high speed rotating to disperse (HSR) and high-energy ball milling to disperse (HEBM).…”
Section: Hebm In Thermoplastic Matrix Compositesmentioning
confidence: 99%